Taṭbīq Wasīlah al-Ṣūrah Litarqiyyah Raghbah Taʻallum al-Lughah al-ʻArabiyyah Litalāmīdh fī al-Madrasah al-Mutawassiṭah Guppi Tanjung Harapan - Isnawanti; Ira Aniati (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
Students of MTsS Guppi Tanjung Harapan do not like Arabic language learning, Arabic language learning is less varied than other foreign language, teachers still use monotonous methods so that students are bored and consider Arabic language difficult. So with problems, the researcher used picture media in learning Arabic for students at MTsS Guppi Tanjung Harapan. This type of research of classroom action research, which is carried out through two cycles. Using the Kemmis & Taggart model, with name: planning, implementation, observation and reflection. Data collection technique uses questionnaires and observations. The results of the study showed that:1 use of picture media runs in the very good category. Proven by increasing the results of teacher and student activities. In cycle I, teacher activity obtained 76, then increased to 95 cycle II. While the value of student activity cycle I obtained 66 , then increased to 91 cycle II. 2 Student interest is running with a very strong category. This is proven by the increase student learning interest, namely in cycle I student learning interest obtained an average value of 75.4% and in cycle II the average value was 91.3% meaning an increase of 15.9%, So with result the target was achieved. العديد من التلاميذ في المدرسة المتوسطة جوبي تانجونج هارابان لا يحبون تعلم اللغة العربية. تعلم اللغة العربية فيها أقل تنوعًا بالنسبة إلى تعلم اللغات الأجنبية الأخرى، المعلمون يستخدمون أساليب رتيبة مثل أساليب المحاضرات، ذلك مما يجعل التلاميذ يشعرون بالملل ويعتقدون أن تعلم اللغة العربية أمر صعب. في مثل هذه المشكلات، استخدم الباحث وسيلة الصورة لترقية رغبة تعلم اللغة العربية لدى تلاميذ الصف السابع في المدرسة المتوسطة جوبي تانجونج هارابان. هذا البحث نوع من البحث الإجرائي في الفصول الدراسية باستخدام نموذج kemmis & taggart، ويتم الإجراء من خلال دورتين. ويتكون الإجراء من 4 مراحل وهي: التخطيط، والتنفيذ، والملاحظة، والانعكاس. التقنية جمع البيانات المستخدمة الاستبيان والملاحظة. أظهرت نتائج البحث أن: (1) استخدام وسيلة الصورة يقع في درجة جيد جدًا. ويتجلى من خلال ترقي نتائج نشاط المعلم والتلاميذ. وفي الحلقة الأولى حصل نشاط المعلم على 76، ثم ارتفع إلى 95 في الحلقة الثانية. في حين كانت درجة نشاط التلاميذ في الحلقة الأولى 66، ثم ارتفعت إلى 91 في الحلقة الثانية. (2) رغبة التلاميذ في تعلم اللغة العربية يقع في درجة قوية جدًا. ويتجلى ذلك من خلال ترقي رغبة التلاميذ في التعلم، وبالتحديد في الحلقة الأولى حصلت رغبة التلاميذ في التعلم على متوسط ​​درجات 75.4%، وفي الحلقة الثانية كان متوسط ​​الدرجات 91.3%، أنه قد ارتفع متوسط درجات رغبة التلاميذ بالنسبة 15.9%، وبهذه النتيجة تم تحقيق الهدف.